Capabilities of Blended Learning as a Teaching and Learning Tool in Tikrit University - Abdullah Ibraheem (Tikrit Journal of Pure Science)
In early 2022, After the COVID-19 pandemic, many universities around the world, especially Iraqi universities, continued offering online courses based on a blended learning approach that supporting by traditional learning. The growing demand and popularity of mixed-learning models in higher education has made them a widespread educational phenomenon. However, most of the literature focus on blended learning design techniques only without considering interrelated key components for user needs and how to design blended learning based on user interaction (UI), user experience (UX), and different cultures and languages of learners. Therefore, this research aims to the evaluation of BL at Tikrit University based on the needs, and interactions of students in the learning process. Therefore, This study is an experimental study based on questionnaires distributed to 180 students from different colleges at Tikrit University. Finally, the results show that learning and acquiring skills and knowledge through BL is preferable to learning through traditional classrooms.